Living together as equals the demands of citizenship - Mason, Andrew, 1959- (Oxford : Oxford University Press, 2012)
There is considerable debate about the demands citizenship places upon us in our everyday lives. 'Living Together as Equals' distinguishes two different ways of thinking about citizenship both of which shed some light on the demands that it makes upon us.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Citizenship